HUBUNGAN MASA KERJA DAN SIKAP KERJA DENGAN KEJADIAN CARPAL TUNNEL SYNDROM PADA PEKERJA PEMBUAT KERUPUK DI INDUSTRI PEMBUAT KERUPUK AHAK KECAMATAN SUNGAILIAT PROVINSI BANGKA BELITUNG TAHUN 2016 - Muhammad Yunus; Neno Fitriyani Hasbie; Gusti Rian Tami (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2019)
Background: Unnatural and ergonomic working attitude for a long time can cause various health problems inworkers one of them is a movement disorder in certain body parts such as hands or called as musculoskeletal.One of musculoskeletal disorders is carpal tunnel syndrome. Crackers makers do repetitive movements, handmovements with strength, flexion and extension, static hand positions, the position of the upper body andlower are not ergonomic, causing stress to the tissue surrounding the carpal tunnel. The purpose of this studyis to determine the relationship of working time and attitude among crackers makers in ahak crackers industry.Methods: An analytical survey with cross sectional approach. The total of sample was 38 respondents. Thestudy was done by spreading questionnaires and doing phalen test measurement. The data was analyzed by chisquare tests.Result : Research shows that respondents with tenure ≥ 4 years as many as 24 people ( 63. 2% ) and with high-risk work attitude as many as 27 people ( 71.12 % ), and then From 38 respondents,25 were having Carpal Tunnel Syndrome. The result showed the relationship between working time (p=0.000< 0,05 and 0R=17,5), working attitude (p= 0.000< 0,05 and OR=25,875) with Carpal Tunnel Syndromeincidences.Conclusion: There is relationship Between Working Time And Attitude With Carpal Tunnel SyndromeIncidences Among Workers In Ahak Crackers Industry Sungailiat Bangka Belitung Province 2016